2007
DOI: 10.1086/525847
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Current-Sheet-like Structures in the Solar Wind

Abstract: In past years, measurements of the solar wind plasma have advanced our understanding of MHD turbulence tremendously. At small scales, the solar wind is believed to be ve'xry multifractal with nonlinear interactions causing an intermittent energy dissipation, leading to possible current-sheet structures. In this Letter, we propose a systematic data analysis procedure to examine the existence of current sheets in the solar wind. We show that by studying the integrated distribution function of the angle between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 13 publications
2
105
0
Order By: Relevance
“…This showed that PIC simulations can reproduce MHD results at large scales. Both simulations showed formation of thin current sheets, which are also observed in solar wind plasmas [6]. The lengths of the current sheets scaled linearly with the driving scale of turbulence, in both MHD and PIC.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…This showed that PIC simulations can reproduce MHD results at large scales. Both simulations showed formation of thin current sheets, which are also observed in solar wind plasmas [6]. The lengths of the current sheets scaled linearly with the driving scale of turbulence, in both MHD and PIC.…”
Section: Introductionmentioning
confidence: 61%
“…Recent observations of solar wind show the energy cascade even extending from the ion scales to the electron scales [5]. At the same time, current sheets are also observed in the solar wind [6]. These current sheets can also dissipate energy through the mechanism of magnetic reconnection [7].…”
Section: Introductionmentioning
confidence: 98%
“…An open question is to determine the fraction of these structures that have developed in the solar wind during propagation or are relics of coronal phenomena. Borovsky (2008) and Li (2008) have shown that magnetic discontinuities in the solar wind may be fossil structures originating from the solar surface related to granule and supergranule structure on the Sun. Plasma structures and boundaries over a range of radial distances allow us to directly address the evolution of structures from the corona into the solar wind.…”
Section: Sources Of the Solar Windmentioning
confidence: 99%
“…For comparison, we also perform the same analysis when Cluster C1 is in the solar wind. Using a data analysis procedure first introduced in Li (2007Li ( , 2008, we find that current-sheet-like structures can be clearly identified in the solar wind. However, similar structures do not exist inside the Earth's magnetotail.…”
mentioning
confidence: 96%